Parallel effect of 4-octylphenol and cyclic adenosine monophosphate (cAMP) alters steroidogenesis, cell viability and ROS production in mice Leydig cells. (May 2018) - Jambor, Tomas; Greifova, Hana; Kovacik, Anton; Kovacikova, Eva; Tvrda, Eva; Forgacs, Zsolt; Massanyi, Peter; Lukac, Norbert
Abstract: Over the last decade, there is growing incidence of male reproductive malfunctions. It has been documented that numerous environmental contaminants, such as endocrine disruptors (EDs) may adversely affect the reproductive functions of humans as well as wildlife species. The aim of this in vitro study was to examine the effects of 4-octylphenol (4-OP) on the steroidogenesis in mice Leydig cells. We evaluated the impact of this endocrine disruptor on the cholesterol levels and hormone secretion in a primary culture. Subsequently, we determined the cell viability and generation of reactive oxygen species (ROS) following 4-OP treatment. Isolated mice Leydig cells were cultured in the presence of different 4-OP concentrations (0.04–5.0 μg/mL) and 1 mM cyclic adenosine-monophosphate during 44 h. Cholesterol levels were determined from the culture medium using photometry. Quantification of steroid secretion was performed by enzyme-linked immunosorbent assay. The cell viability was assessed using the metabolic activity assay, while ROS production was assessed by the chemiluminescence technique. Slightly increased cholesterol levels were recorded following exposure to the whole applied range of 4-OP, without significant changes (P>0.05) . In contrast, the secretion of steroid hormones, specifically dehydroepiandrosterone, androstenedione, and testosterone was decreased following exposure to 4-OP. Experimental doses of 4-OP did not affect cell viability significantly; however a moderate decrease was recorded following the higher doses (2.5 and 5.0 μg/mL) of 4-OP. Furthermore, relative treatment of 4-OP (5.0 μg/mL) caused a significant (P  <  0.001 ) ROS overproduction in the exposed cells. Graphical abstract: Image 1 Highlights: 4-OP does not significantly affect cAMP-stimulated cholesterol quantity. 4-OP together with cAMP are able to decrease the biosynthesis of steroid hormones. cAMP- stimulated Leydig cell viability was decreased after 44 h of treatment. 4-OP caused a significant intracellular production of ROS after 44 h of incubation.